Establish a perioperative check forum for peripheral intravenous access to prevent the occurrence of phlebitis. Issue 4 (5th March 2015) - Chiu, Po‐Chun; Lee, Ya‐Hui; Hsu, Hung‐Te; Feng, Yu‐Tung; Lu, I‐Cheng; Chiu, Shun‐Li; Cheng, Kuang‐I
Abstract: The prevalence of intravenous (IV) catheter‐related infections is 0.5 per 1000 device days, and these infections cause tenderness, erythema, swelling and phlebitis. Catheter‐related bloodstream infections (CRBSI) may independently increase hospital costs and length of stay; the aim of the study was to set up a standard operating procedure (SOP) for the maintenance of peripheral vein catheter patency and the prevention of IV catheter‐related complications. This is a retrospective study, enrolling patients who received anesthesia between April 2010 and January 2011. The study included 1 month of pretest phase, and 3 months each of "notification" phase, "observation" phase and "end" phase, respectively. The cannulations were set up by surgical ward nurses following the SOP on establishing peripheral intravenous catheter in our hospital. The cannulation sites were then examined before surgery and postoperatively by registered nurse anesthetists using the Baxter Scale. We also tried to set up a feedback circuit to let ward nurses know about the IV patency rate. As a result, 14, 682 patients were enrolled in the study. The incidence of IV therapy‐related adverse events was 0.78% in the notification phase, 0.43% in the observation phase, and 0.13% in the end phase. Overall IV therapy‐related events declined significantly ( p < 0.01), and the presence of phlebitis was associated with age ( p < 0.05). An SOP established to assess IV patency through a checklist can reduce phlebitis and improve quality. The checklist increases ward nurses' and nurse anesthetists' awareness of IV patency, and the feedback circuit substantially reduces IV event rate.